Development of Generic Science Skills Assessment Instruments for Chemistry Practicum on Thermochemistry and Reaction Rate - Anisa Fauziyah; Suwahono; Wiwik Kartika Sari (JPP (Jurnal Pendidikan dan Pembelajaran), 2023)
Science Generic skills are essential skills that must be mastered by students. Science generic skills can be assessed when students carry out practical activities through performance assessments. This study aims to develop an instrument based on general science in chemistry practicums on thermochemistry and reaction rates. This study was R&D with the ADDIE model, namely analysis, design, development, implementation, and evaluation. The instruments used are validation sheets, reliability test sheets, and questionnaires. The results of data analysis showed that the instrument developed was valid, with an average score of 0.89 in a very good category. The results of the reliability test have a reliable category with an average intraclass correlation coefficient (ICC) for the thermochemistry practicum of 0.766 and a reaction rate of 0.80, while the average values for the two labs are 0.903 and 0.921. The results of the practicality test showed that the percentage of positive responses was 91.29%, so it can be stated that the product has a practical category. Based on the result, the science generic skills instruments can be used in the assessment of thermochemistry and reaction rates in the practicum because they meet the valid, reliable, and practical requirements.